Draft Annual Plan 1988-89 Jammu and Kashmir - Planning Commission (Planning Commission, 1987)
The 7th Five Year Plan for the State of J&K is approved at Rs. 1400 crores out of which Rs. 215.77 crores is the estimated requirement on account of maintenance cost of schemes that were completed in the 6th plan period but on account of paucity of resources a portion of the financial requirements was carried over to the 7th plan. The net investment expected to be made for the 7th Five Year Plan period is, therefore, of the order of Rs. 1184.23 crores at 1984-85 prices. The growth rate of the economy is fixed at 4.5% per annum.
Jammu and Kashmir, Planning and Development Department